2023
DOI: 10.1002/agj2.21280
|View full text |Cite
|
Sign up to set email alerts
|

Intercropping chickpea–flax for yield and disease management

Abstract: This article has been accepted for publication and undergone full peer review but has not been through the copyediting, typesetting, pagination and proofreading process, which may lead to differences between this version and the Version of Record. Please cite this article as

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…Foliar crop diseases, such as mycosphaerella blight of pea (Fernández-Aparicio et al 2010;Schoeny et al 2010), ascochyta blight of chickpea (Zhou et al 2023), and chocolate spot of faba beans (Fernández-Aparicio et al 2011;, have been reduced through intercropping. Lower levels of foliar disease likely diminish the need for fungicide application, thereby providing further economic advantages.…”
Section: Successesmentioning
confidence: 99%
“…Foliar crop diseases, such as mycosphaerella blight of pea (Fernández-Aparicio et al 2010;Schoeny et al 2010), ascochyta blight of chickpea (Zhou et al 2023), and chocolate spot of faba beans (Fernández-Aparicio et al 2011;, have been reduced through intercropping. Lower levels of foliar disease likely diminish the need for fungicide application, thereby providing further economic advantages.…”
Section: Successesmentioning
confidence: 99%
“…Several studies have demonstrated that intercropping can significantly reduce the incidence and severity of various diseases. For example, intercropping chickpea with flax suppressed Ascochyta blight, which is a worldwide constraint for chickpea production ( Zhou et al., 2023 ). Similar results reported that intercropping can effectively control foliar and soil-borne diseases in CSFL crops ( Schoeny et al., 2010 ; Mousa and El-Sayed, 2016 ; Zhang et al., 2019 ; Lv et al., 2020 ).…”
Section: Cool-season Food Legumes In the Intercropping Systemmentioning
confidence: 99%
“…In 2020 alone, 102,000 acres were planted, with 99,200 acres harvested [12]. Despite the economic importance of chickpea cultivation in Montana, this pulse crop faces distinctive challenges arising from biotic factors [13]. The prevalence of soil-borne pathogens, particularly Fusarium spp., is a significant hurdle that contributes to yield-limiting factors in cropping systems worldwide [14].…”
Section: Introductionmentioning
confidence: 99%